DIETARY HABIT AND LIFESTYLE PRACTICES AMONG NORMAL AND OVERWEIGHT/OBESE IIUM KUANTAN STUDENTS: A COMPARATIVE STUDY - MOHD FAUZY @ MOHD ALI, NUR KAMILAH; JAAFAR, NURUL HAZIRAH (International Journal of Allied Health Sciences, 2020)
Introduction: The prevalence of overweight and obesity has been increasing throughout the year among all age groups including young adult. Young adults who recently entered university life are prone to become overweight /obese due to their unhealthy eating behaviour and lifestyle practices. Hence, this study was conducted to estimate the prevalence of overweight/obesity and determine the association of eating habits and lifestyle practices between BMI status of students in International Islamic University Malaysia (IIUM) Kuantan campus. Methods: A total of 120 students from IIUM Kuantan Campus participated in this study. Their weight and height were measured, and self-reported questionnaires adapted from a previous study on eating habits, lifestyle practices and knowledge of food pyramid were collected (Yun, A, David, & Quee, 2018). Then, the data was compared between normal and overweight / obese participants. Results: The prevalence of overweight and obesity among IIUM Kuantan students was 42.5% (51 out of 120) (95% CI : 24.2%, 26.1%). Most participants reported to snacks in between meals, had frequent intake of vegetables and fried foods, and low intake of fruits in their diet. However, it failed to prove significant association between these dietary practices with BMI status. The preferences of having cheaper food was significantly higher in overweight / obese (p=0.001). Less than half of the participants (41.7%) exercised every day or frequently. The result showed significant association between exercise and BMI status (p = 0.049), whereby a higher proportion of normal weight population (28.3%) exercised every day or frequently Conclusions: There is high prevalence of overweight and obesity noticeable among the IIUM Kuantan students and most of them had poor dietary habit and unhealthy lifestyle practices. For future research, formulating suitable intervention to improve lifestyle behaviour among university students is highly needed. KEYWORDS: Dietary habit, Lifestyle practices, Overweight/Obesity, Young Adults, University Students